Sex differences in fear expression and persistence in an animal model of Post-Traumatic Stress Disorder - Riccardi, Eleonora; Mancini, Giulia Federica; Pisaneschi, Arianna; Morena, Maria; Campolongo, Patrizia (Neuroscience, 2024)
•Female rats show faster and more effective trauma extinction than males.•Shock reminder reactivates fear memory only in male rats.•Ultrasonic vocalizations mirror fear behavior profiles in both sexes.•Study underscores the need for female inclusion in preclinical PTSD research. Post-Traumatic Stress Disorder (PTSD) is a complex psychiatric condition arising from traumatic experiences, marked by abnormal fear memories. Despite women are twice as likely as men to develop PTSD, the biological mechanisms underlying this disparity remain inadequately explored, particularly in preclinical studies involving female subjects. Previous research shows that female rats exhibit active fear responses, while males display passive behaviors. Additionally, sex differences in ultrasonic vocalizations (USVs) during fear conditioning have been observed, indicating varying emotional responses. Here, we validated a traumatic stress model consisting of footshock exposure paired with social isolation − originally developed in male rats − on females for the first time, focusing on sex differences in fear memory expression, retention and extinction. Our findings reveal that only during trauma exposure, males predominantly exhibited passive responses, whereas females demonstrated more active responses, despite both sexes emitting similar numbers of alarm USVs. Females also showed lower levels of freezing and USV emissions throughout extinction sessions and displayed a higher extinction rate compared to males. Notably, only males displayed a conditioned fear response when triggered by a single mild stressor. These findings highlight sex differences in trauma responses and fear memory processes. The study emphasizes the importance of incorporating 22-kHz USV evaluations along with other behavioral metrics for a comprehensive understanding of fear memory. This research contributes to the existing literature on traumatic stress models as well as underscores the necessity of including female subjects in preclinical studies to better inform treatment and prevention strategies tailored to both sexes.